ANALYZING THE EVOLVING CONSUMER PREFERENCES IN CHINA’S FURNITURE MARKET USING THE STIMULUS-ORGANISM-RESPONSE MODEL: A SYSTEMATIC REVIEW - Wang, J.; Wahab, M. H. A.; Zhan, H.; Nor, O. M. (Journal of Engineering and Technology (JET), 2025)
The furniture market in China is a blend of traditional craftsmanship and modern innovation, reflecting a shift in consumer preferences. This systematic literature review utilizes the Stimulus-Organism-Response (S-O-R) model to examine the dual influences of traditional cultural and contemporary functionality on consumer behaviour in China’s furniture market.